The design encyclopedia - Byars, Mel, ....-; Museum of Modern Art (New York, N.Y.); Tiley, Terence, ....- (Bussum : Thoth, 2004)
This definitive encyclopedia covers all elements associated with decoration and design in eastern and western Europe, Australia, North and South America and Japan. Over 3000 entries form a compendium of designers, firms, movements, styles and materials in the design world from the 19th century to the present. Features lists of major design exhibitions and fairs worldwide, ranging from the 1851 Great Exhibition in London through the 1992 Seville Expo to a Pan-Russian Exhibition in Moscow in 1882. Every entry includes dates, biography, details of design education and influences, exhibitions and awards, an in-depth discussion of important designs plus a complete bibliography covering publications in all languages.
Keywords: Industriële vormgeving